2023
DOI: 10.1111/1467-8454.12301
|View full text |Cite
|
Sign up to set email alerts
|

Risk contagion in financial markets: A systematic review using bibliometric methods

Abstract: We explore evolving research trends and hotspots in financial contagion through keywords co‐occurrence and co‐citation network analyses. 2,071 articles have been collected from Web of Science Core Collection database from 2005 to 2021 and been analyzed by using bibliometric methods. The results indicate a tremendous growth in research on financial contagion, especially following the Global Finance Crisis. The current research mainly focuses on understanding the causes and consequences of past financial crises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…They identified 151 empirical studies, and the results of their analysis indicated that empirical studies on contagion have consistently increased in recent years. Another analysis conducted by Su et al (2023) examines the risk of financial contagion in financial markets. They extracted articles using the Web of Science database for the period 2005-2021.…”
Section: Conceptual Dimensions Of Financial Contagionmentioning
confidence: 99%
“…They identified 151 empirical studies, and the results of their analysis indicated that empirical studies on contagion have consistently increased in recent years. Another analysis conducted by Su et al (2023) examines the risk of financial contagion in financial markets. They extracted articles using the Web of Science database for the period 2005-2021.…”
Section: Conceptual Dimensions Of Financial Contagionmentioning
confidence: 99%
“…‘Risk contagion in financial markets: A systematic review using bibliometric methods’ by Su et al (2024) presents a comprehensive analysis of studies on financial contagion. The analysis highlights a growing interest in risk contagion studies within unconventional assets, such as cryptocurrencies.…”
mentioning
confidence: 99%